Neuroprotective Effect of Optimized Yinxieling Formula in 6-OHDA-Induced Chronic Model of Parkinson's Disease through the Inflammation Pathway. (21st December 2019) - Wei, Renrong; Rong, Cuiping; Xie, Qingfeng; Wu, Shouhai; Feng, Yuchao; Wang, Ruihua; Dai, Zhenhui; Lin, Tongxiang
Abstract : Parkinson's disease (PD) is characterized by progressive degeneration of dopaminergic neurons in the substantia nigra (SN)-striatum circuit, which is associated with glial activation and consequent chronic neuroinflammation. Optimized Yinxieling Formula (OYF) is a Chinese medicine that exerts therapeutical effect and antiinflammation property on psoriasis. Our previous study has proven that pretreatment with OYF could regulate glia-mediated inflammation in an acute mouse model of PD induced by 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine. Given that PD is a chronic degeneration disorder, this study applied another PD animal model induced by striatal injection of 6-hydroxydopamine (6-OHDA) to mimic the progressive damage of the SN-striatum dopamine system in rats. The OYF was administrated in the manner of pretreatment plus treatment. The effects of the OYF on motor behaviors were assessed with the apomorphine-induced rotation test and adjusting steps test. To confirm the effect of OYF on dopaminergic neurons and glia activation in this model, we analyzed the expression of tyrosine hydroxylase (TH) and glia markers, ionized calcium-binding adapter molecule 1 (Iba-1), and glial fibrillary acidic protein (GFAP) in the SN region of the rat PD model. Inflammation-associated factors, including tumor necrosis factor- α (TNF- α ), interleukin-1 β (IL-1 β ), IL-6, inducible nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX-2), were further evaluated in this model and in interferon- γ - (INF- γ -) induced murine macrophages RAW264.7 cells. The results from the in vivo study showed that OYF reversed the motor behavioral dysfunction in 6-OHDA-induced PD rats, upregulated the TH expression, decreased the immunoreactivity of Iba-1 and GFAP, and downregulated the mRNA levels of TNF- α and COX-2. The OYF also trended to decrease the mRNA levels of IL-1 β and iNOS in vivo . The results from the in vitro study showed that OYF significantly decreased the mRNA levels of TNF- α, IL-1 β, IL-6, iNOS, and COX-2. Therefore, this study suggests that OYF exerts antiinflammatory effects, which might be related to the protection of dopaminergic neurons in 6-OHDA-induced chronic neurotoxicity.